ANALISIS USAHATANI RUMPUT LAUT DI KECAMATAN NAGAWUTUNG KABUPATEN LEMBATA - Asnah Asnah; L. Latu (Universitas Tribhuwana Tunggadewi, 2012)
Seaweed cultivation is one of cultivation in fishery have been increased, especially in waters of Indonesia. The aims of this research were to study the cost, revenue, income, profit, and economic efficiency of seaweed business in Nagawutung Sub District, Lembata Regency. The sample was gained by simple randomized sampling i.e. 30 farmers. The data collected were analyzed by using simple statistic analysis. The research result showed the total of cost in average in seaweed business was IDR 1,662,920.83; revenue in average was IDR 19,800,000; income in average was IDR 18,943,412.50; and profit in average was IDR 18,137,079.17. Economic efficiency value based on analysis B/C was 11.36. The value of BEP was 184.77 kg, and price BEP was IDR 803.70/kg. It is be concluded that seaweed business in Nagawutung Sub District, Lembata Regency was efficient, profitable and useful for the farmers